PENGARUH PENGGUNAAN IKLAN DAN ELECTRONIC WORD OF MOUTH DI APLIKASI TIKTOK MELALUI CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE SCARLETT WHITENING DI KOTA PEKANBARU - Putri Rahma Suci; Jushermi Jushermi; Rahayu Danar Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the influence of the use of Advertising and ElectronicWord of Mouth in Tiktok application through Brand Image on PurchasingDecisions for Scarlett Whitening skincare products in Pekanbaru City. Thepopulation in this study are consumers of Scarlett Whitening skincare products inPekanbaru City who use Tiktok. The sample in this study amounted to 100samples using the purposive sampling method. Primary data was collected byquestionnaire as an instrument to prove the results of the research, to test thehypothesis in this study is using path analysis with SPSS version 25.0. The resultsshowed that : 1) Advertising in Tiktok application has a positive and insignificanteffect on Brand Image of Scarlett Whitening skincare products in Pekanbaru City,2) e-WOM in Tiktok application has a positive and significant effect on BrandImage of Scarlett Whitening skincare products in Pekanbaru City, 3) Advertisingin Tiktok application has a positive and significant effect on Purchasing Decisionof Scarlett Whitening skincare products in Pekanbaru City, 4) e-WOM in Tiktokapplication has a positive and significant effect on Purchasing Decision ofScarlett Whitening skincare products in Pekanbaru City, 5) Brand Image has apositive and significant effect on Purchasing Decision of Scarlett Whiteningskincare products in Pekanbaru City, 6) Advertising in Tiktok application throughBrand Image has no significant effect on Purchasing Decision of ScarlettWhitening skincare products in Pekanbaru City.7) e-WOM in Tiktok applicationthrough Brand Image has a positive and significant effect on Purchasing Decisionof Scarlett Whitening skincare products in Pekanbaru City. Keywords : Advertising, Electronic Word of Mouth, Brand Image, PurchaseDecision